Socioeconomic Inequities in the Health and Nutrition of Children in Low/Middle Income Countries - Barros, F. C.; Victora, C. G.; Scherpbier, R.; Gwatkin, D. (2012)
OBJECTIVE: To describe the effects of social inequities on the health and nutrition of children in low and middle income countries. METHODS: We reviewed existing data on socioeconomic disparities within-countries relative to the use of services, nutritional status, morbidity, and mortality. A conceptual framework including five major hierarchical categories affecting inequities was adopted: socioeconomic context and position, differential exposure, differential vulnerability, differential health outcomes, and differential consequences. The search of the PubMed database since 1990 identified 244 articles related to the theme. Results were also analyzed from almost 100 recent national surveys, including Demographic Health Surveys and the UNICEF Multiple Indicator Cluster Surveys. RESULTS: Children from poor families are more likely, relative to those from better-off families, to be exposed to pathogenic agents; once they are exposed, they are more likely to become ill because of their lower resistance and lower coverage with preventive interventions. Once they become ill, they are less likely to have access to health services and the quality of these services is likely to be lower, with less access to life-saving treatments. As a consequence, children from poor family have higher mortality rates and are more likely to be undernourished. CONCLUSIONS: Except for child obesity and inadequate breastfeeding practices, all the other adverse conditions analyzed were more prevalent in children from less well-off families. Careful documentation of the multiple levels of determination of socioeconomic inequities in child health is essential for understanding the nature of this problem and for establishing interventions that can reduce these differences.